A Study on Online Shopping Cart Abandonment: A Product Category Perspective. Issue 4 (2nd October 2019) - Song, Jae-Do
Abstract: Consumer behavior and decision processes can differ according to product characteristics. To determine the characteristics that lead to explaining online shopping cart abandonment, this study adopts product categories as the unit of analysis and identifies product categorization variables and motivations for various shopping activities. The results of the present analysis indicate that among the motivations for shopping activities, deliberation, offline physical inspection, and hedonic shopping value have significant effects on cart abandonment. Among the product categorization variables, price, perceived importance, symbolic value, experience attribute, and purchase frequency have indirect significant effects on cart abandonment through the motivations for shopping activities. Finally, price has a direct effect on cart abandonment.